2013
DOI: 10.1536/ihj.54.266
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Coronary Artery Stenosis at Rest in Patients With Normal Left Ventricular Wall Motion

Abstract: SummaryNoninvasive detection of coronary artery stenosis usually requires a stress test in patients without left ventricular (LV) regional wall motion abnormalities (RWMA). In contrast, abnormal regional LV relaxation caused by ischemia may persist beyond recovery from transient ischemia. The aim of the present study was to determine whether segmental analysis of abnormal regional LV relaxation using the strain imaging diastolic index (SI-DI) at rest could predict coronary artery stenosis in the three major ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…Several studies have reported that longitudinal strain measured by 2DST echocardiography at rest was significantly lower in patients with advanced CAD and may be useful marker for detecting CAD . Our study demonstrated that SAX radial strain measured by 2DST also may be useful for detecting CAD.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Several studies have reported that longitudinal strain measured by 2DST echocardiography at rest was significantly lower in patients with advanced CAD and may be useful marker for detecting CAD . Our study demonstrated that SAX radial strain measured by 2DST also may be useful for detecting CAD.…”
Section: Discussionsupporting
confidence: 64%
“…And in rare case, cardiovascular complications such as myocardial infarction, severe arrhythmias, and even sudden death can occur. Several studies have reported that longitudinal strain measured by 2DST echocardiography at rest was significantly lower in patients with advanced CAD and may be useful marker for detecting CAD …”
mentioning
confidence: 99%
“…In the setting of an emergency room, however, simple, rapid, and accurate methodologies to detect myocardial ischemia are required in patients with acute coronary syndrome, 9,10) as adequate medical treatment or coronary revascularization can improve the prognosis. The present case highlights the use of ischemic QRS axis deviation tendency to indicate ischemic heart disease, including left main trunk disease.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we cannot arrive at any conclusion from this study, except to state that the prevalence of CAD is probably lower in populations with a high EPA/AA ratio. Third, because determination of the presence of CAD in this study population relied on the findings of coronary angiography, the existence of subjects in the study population of undetected cases of asymptomatic CAD which can be diagnosed primarily by an exercise stress test or non-invasive tests 31) such as coronary artery computed tomography cannot be ruled out. Fourth, because this study was a pilot cross-sectional single-center study involving a relatively small number of subjects and there were missing test data for 51 of the 700 consecutive cases, we cannot rule out the existence of case selection bias.…”
Section: )mentioning
confidence: 99%